Metabolites of Mangrove Sediment Bacteria from Semarang and Karimunjawa as Anti-Fungal and Antibacterial - Pringgenies, Delianis; Setyati, Wilis Ari (Trends in Sciences, 2023)
Pathogenic bacteria are microorganisms that cause disease in humans because bacteria grow cosmopolitan with human life, both on land and underwater. This research aimed to obtain mangrove sediment bacteria that have the potential as antibacterial and antifungal bacteria from mangrove sediments in Semarang and Karimunjawa waters. Mangrove sediment bacteria that have the potential as antibacterial and antifungal bacteria from Semarang and Karimunjawa waters, as well as identification of their compounds using the GCMS method. Sediment samples were collected from Semarang and Karimunjawa, and bacterial screening and isolation were then carried out. Bacterial isolates were tested with pathogenic fungi Malassezia furfur and Candida albicans. As well as the pathogenic bacteria Staphylococcus aureus, Escherichia coli, and Staphylococcus typhi. Then, the potential bacteria were identified by the molecular DNA method and analyzed by the GC-MS method to determine the secondary metabolite compounds that act as antifungal and antibacterial. The results showed that the bacterial isolation of mangrove sediments from Karimunjawa and Semarang that had antibacterial activity against pathogenic bacteria E. coli, S. aureus, and S. typhi were 3 isolates, namely SKK 1 MA, SKS 2 ISP, and SKS 4 ISP. The 3 isolates also had antifungal activity against the fungal pathogens Malassezia furfur and Candida albicans. The molecular identification showed that the 3 potential isolates, namely SKK 1 MA, SKS 2 ISP, and SKS 4 ISP, were Bacillus sp., Bacillus cereus, and Alcaligenes faecalis, respectively. Results of the analysis of the content of bacteria as antifungal and antibacterial showed that the bacteria were dominated by the content of unsaturated fatty acids (omega 9) and saturated fatty acids. HIGHLIGHTS Pathogenic fungal infections are difficult to treat besides infections caused by pathogenic bacteria Natural substances produced by microorganisms are very diverse in structure and are an essential source in the search for new drugs for various diseases in humans, including infections by pathogenic fungi and pathogenic bacteria The mangrove sediment bacteria were found to have potential as antifungal and antibacterial and were proven to contain fatty acids Bacteria found to be useful as antifungal and antibacterial agents for various bio-industrial activities GRAPHICAL ABSTRACT